2022
DOI: 10.1002/agj2.21002
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional analysis of mitogen‐activated protein kinases 6 gene in lettuce

Abstract: Lettuce (Lactuca sativa L.) being a cool‐season crop can bolt if the temperatures increase above 20 °C. When lettuce bolts, the plants start the reproductive growth cycle. The improvement in resistance to high temperature bolting has been an important goal of lettuce breeding. This paper verified that Lactuca sativa mitogen‐activated protein kinases 6 (LsMAPK6) played an important role in high temperature bolting. The full‐length CDS of LsMAPK6 gene was amplified by real‐time polymerase chain reaction (RT‐PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…MAPK signaling pathway has been known for its roles in stimulus signals transduction, including heat and cold stresses, and pathogen infections (Zhang & Storey 2017; Ding et al 2018; Zhan et al 2018; Muhammad et al 2019; Wang et al 2019; Su et al 2020). Compared with vertebrates and other higher invertebrates, the functions researches about the MAPK pathway genes in phytoseiid mites are far behind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAPK signaling pathway has been known for its roles in stimulus signals transduction, including heat and cold stresses, and pathogen infections (Zhang & Storey 2017; Ding et al 2018; Zhan et al 2018; Muhammad et al 2019; Wang et al 2019; Su et al 2020). Compared with vertebrates and other higher invertebrates, the functions researches about the MAPK pathway genes in phytoseiid mites are far behind.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signaling pathway is mainly composed of three subfamilies including C-Jun N-terminal kinase (JNK), p38 and extracellular signal-regulated kinase (ERK). It has been shown that adaptive responses to elevated temperature exposure by activation of JNK, p38 and ERK (Gourgou et al 2010; Wang et al 2019). Heat stress treatment (43°C) could significantly induce the phosphorylation of the JNK, p38 and ERK signal proteins, as well as increasing the production of HSP70 (heat shock protein 70) in rat small intestine (Hao et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Innovative studies using PCR analysis were made in lettuce (Lactuca sativa L.) by T. Wang, Liu, et al (2022) and in Cyclocarya paliurus Iljinskaja, a special plant species grown at high elevation in southwestern China, by . The authors noted that GAPDH gene was identified as the best reference gene.…”
Section: Environmental Factors Affecting Crop Production and Qualitymentioning
confidence: 99%